Microfluidic preparation of polymer nanospheres - Kucuk, Israfil; Edirisinghe, Mohan (Springer, 2014)
In this work, solid polymer nanospheres with their surface tailored for drug adhesion were prepared using a V-shaped microfluidic junction. The biocompatible polymer solutions were infused using two channels of the microfluidic junction which was also simultaneously fed with a volatile liquid, perfluorohexane using the other channel. The mechanism by which the nanospheres are generated is explained using high speed camera imaging. The polymer concentration (5-50 wt%) and flow rates of the feeds (50-300 mu l min(-1)) were important parameters in controlling the nanosphere diameter. The diameter of the polymer nanospheres was found to be in the range of 80-920 nm with a polydispersity index of 11-19 %. The interior structure and surfaces of the nanospheres prepared were studied using advanced microscopy and showed the presence of fine pores and cracks on surface which can be used as drug entrapment locations.
Keywords: Polymethylsilsesquioxane; Perfluorohexane; Microfluidics; Surface morphology; Nanopheres; Nanocarriers; Nanobiotechnology